Cladribine: Off-label disease modification for people with multiple sclerosis in resource-poor settings?. Issue 2 (June 2018) - Mao, Zhifeng; Álvarez-Gonzalez, César; De Trane, Stefania; Yildiz, Ozlem; Albor, Christo; Doctor, Gabriel; Soon, Derek; Pepper, George; Turner, Benjamin P; Marta, Monica; Mathews, Joela; Giovannoni, Gavin; et al.
Background: A considerable number of people with multiple sclerosis (pwMS) live in low- and middle-income countries (LMIC), where lack of resource adversely affects access to effective disease-modifying treatment. Objective: The objective of this commentary is to propose a useful cost-effective disease-modifying treatment option for pwMS in LMIC with potential high efficacy and high convenience to the pwMS and treating physician. Viewpoint : We propose using generic 2-chloro-2'-deoxyadenosine (cladribine), a small molecule licensed for treatment of people with hairy cell leukaemia, as a solution of this significant equity imbalance. Cladribine has been shown in phase II and III trials to be a highly effective disease-modifying treatment for pwMS, and its adverse effect profile is comparable with any DMT currently licensed in high-income economies where an oral preparation has recently been licensed by the European Medicines Agency. Conclusion: Our viewpoint takes into account experience we have gathered over the past three years in the use of generic cladribine to treat pwMS. Whilst here we focus on MS, there is significant potential for use of cladribine in other conditions that could benefit from its mechanism of action.